Insect (Hexapoda) diversity in the oceanic archipelago of Fernando de Noronha, Brazil: Pipunculidae (Diptera) - Rafael, José A.; Marques, Dayse W. A.; Silva-Neto, Alberto M.; Limeira-de-Oliveira, Francisco (Entomological Communications, 2021)
Eudorylas lepus (Rafael, 1990) is recorded for the first time in Fernando de Noronha. It is recorded in low number of specimens and it is shortly characterized.